Design and implementation of a reflow oven for SMD soldering - Korkmaz, Caner. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
Reflow soldering is a process in which components that are placed onto the solder paste applied PCB, are assembled by carefully heating the assembly in order to solder the joints. The assembly may be heated by several methods but the convection reflow seems a prevailing alternative because of its effectiveness in heat transfer and insensitivity to material type or color. Hence, a cheap and industry standard conforming design and implementation of convection reflow oven by using a standard kitchen oven is aimed in this study. For process control, several control algorithms were applied and their results were compared.
Keywords: Surface mount technology.; Solder and soldering.